1981
DOI: 10.1111/j.1365-2621.1981.tb04199.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidified Processing and Storage on Carotenoids (Provitamin A) and Vitamin C in Mung Bean Sprouts

Abstract: Blanching of mung bean sprouts has little effect on total carotenoids and p-carotene. Canned sprouts stored at RT for 6 months lost smaller amounts of total and 'active' carotenoids compared with bottled sprouts. Blanching resulted in approximately 50% loss of vitamin C in fresh mung bean sprouts but storage temperatures alone produced little change in vitamin C.Canned sprouts stored at RT for 6 months contained only 30% of the vitamin C of stored bottled sprouts. Fresh mung bean sprouts contained 19 pg 100 g-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Degradation appeared to involve direct oxidation rather than isomerization of the carotenes. Farhangi and Valadon (1981) also observed degradation of carotenoids without isomerization during acid processing and storage of mung bean sprouts.…”
Section: Results St Discussionmentioning
confidence: 80%
“…Degradation appeared to involve direct oxidation rather than isomerization of the carotenes. Farhangi and Valadon (1981) also observed degradation of carotenoids without isomerization during acid processing and storage of mung bean sprouts.…”
Section: Results St Discussionmentioning
confidence: 80%
“…Blanching in hot water (90°C, 60 s) reduced the total microbial count to 2 log CFU/g in mung bean sprouts (17) while preserving the vitamin C content. In contrast, blanching at a temperature above 95 °C for 60 s resulted in 50% loss of vitamin C in mung bean sprouts (42). The mildest treatment conditions (60°C, 30 s) resulted in only a 2-log reduction of the total microbial count in soybean sprouts (125).…”
Section: Physical Interventions: Thermal Inactivationmentioning
confidence: 94%
“…Increasing the treatment time and temperature has adverse effects on the textural and nutritional qualities, respectively, of the products (42,55). Microorganisms are still capable of growth in the product after hot water treatment, so avoiding recontamination and temperature abuse during storage are critical considerations when using this method.…”
Section: Physical Interventions: Thermal Inactivationmentioning
confidence: 99%
“…They constitute a good source of vitamins (it was observed that the content of various vitamins increased markedly during germination, augmenting the nutrient values of the product). Mung bean sprouts have a total carotenoid content of 284 ".,g (100 g fresh wt) -I of which l3-carotene represents 6010 (Farhangi and Valadon, 1981). The carotenoid distribution is shown in Table 22.…”
Section: Mung Beans (Phaseo/us Aureus Roxb) Leguminosaementioning
confidence: 99%
“…The highest retention occurred in fermented beans. The effect of acidified processing and storage on carotenoids in mung bean sprouts was investigated (Farhangi and Valadon, 1981). The results are shown in Tables 22 and 23.…”
Section: Processingmentioning
confidence: 99%